Risk factors for interpersonal conflicts at work - De Raeve, Lore; Jansen, Nicole WH; van den Brandt, Piet A.; Vasse, Rineke M.; Kant, IJmert (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'The main goal of this study was to identify work-related risk factors for the onset of interpersonal conflicts at work. ' ' METHODS ': 'Longitudinal data from the Maastricht Cohort Study on “fatigue at work” (N=9241) were used. After the respondents who reported an interpersonal conflict at baseline were excluded, logistic regression analyses were used to determine the role of several work-related risk factors at baseline in the onset of a conflict with coworkers or supervisors after 1 year of follow-up. ' ' RESULTS ': 'Higher psychological job demands, higher levels of role ambiguity, the presence of physical demands, higher musculoskeletal demands, a poorer physical work environment, shift work, overtime, and higher levels of job insecurity significantly predicted the onset of both a coworker conflict and a supervisor conflict. Higher levels of coworker and supervisor social support, more autonomy concerning the terms of employment, good overall job satisfaction, monetary gratification, and esteem reward significantly protected against the onset of both a coworker conflict and a supervisor conflict. Higher levels of decision latitude and more career opportunities also significantly protected against the onset of a supervisor conflict. ' ' CONCLUSIONS ': 'Several factors in the work environment were related to the onset of interpersonal conflicts at work. Given the rather serious consequences of interpersonal conflicts at work with respect to health and well-being, the observed risk factors can serve as a starting point for effective prevention and intervention strategies in the workplace.
Keywords: coworker conflict; interpersonal conflict; job content; longitudinal study; Netherlands; risk factor; supervisor conflict; terms of employment; work; work conditions; work relations